(untitled) (Revista Contexto & Saúde, 2023)
To verify eating patterns and their association with social, economic and demographic aspects in adolescence. This is a systematic review conducted in the Embase, PubMed, and Web of Science databases, considering the period from August 2011 to August 2021. Of 19,231 articles identified, 15 observational studies met the eligibility criteria adopted. After updating, 16 articles were included. The methodological aspects of the studies were evaluated using the Strobe (Strengthening the Reporting of Observational Studies in Epidemiology) strategy. The protocol was registered in Prospero (Number 42021260595). Four main results can be listed in this systematic review: a) Higher educational level of the mother or father was found to be positively associated with a healthier eating pattern, and lower educational level with a westernized pattern. b) Higher income and family socioeconomic status were associated with both a healthy and unhealthy pattern. c) Lower socioeconomic status was related to a healthy, traditional, westernized pattern. d) The presence of the adolescent’s mother in the household was correlated with a healthier pattern. The studies bring into focus the multiplicity of social, economic, demographic, cultural, political, and environmental factors involved in adherence to a particular dietary pattern among adolescents, highlighting the impact of different scenarios and social and economic inequities on access to healthy and adequate food.